2015
DOI: 10.3109/09513590.2014.995619
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian and uterine development and hormonal feedback mechanism in a 46 XX patient with CYP19A1 deficiency under low dose estrogen replacement

Abstract: Complete aromatase deficiency provides an excellent model of how ovarian and uterine development in relation to E2, LH, FSH and inhibin B feedback progresses from infancy to adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Thirty patients (0.2‐32 years) were included in the review, 8,10‐28 and the specific information is shown in Table 2 and Table S1. Most 46, XX patients were diagnosed in childhood based on virilized external genitalia, and three patients were initially misdiagnosed with CAH because of briefly elevated ACTH or 17α‐OHP levels.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirty patients (0.2‐32 years) were included in the review, 8,10‐28 and the specific information is shown in Table 2 and Table S1. Most 46, XX patients were diagnosed in childhood based on virilized external genitalia, and three patients were initially misdiagnosed with CAH because of briefly elevated ACTH or 17α‐OHP levels.…”
Section: Resultsmentioning
confidence: 99%
“…10 Bone density is reported to be increased upon oestrogen administration. 7,17 The 9.2-year-old girl showed mild low TBLH BMD, and she started oestradiol therapy during the investigation. We will closely monitor her BMD during follow-up.…”
Section: Laboratory Investigationmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though in this aromatase-deficient patient serum inhibin B levels were not measured, it is unlikely that the lack of suppression of the serum FSH level might be related to a low level of serum inhibin B. Accordingly, in a recent aromatase-deficient patient, reported by Burckhardt et al [32], the upper normal serum inhibin B levels detected were unable to suppress serum FSH levels under low E 2 dose treatment. In addition, a high dose of estrogen replacement therapy was required to suppress serum FSH.…”
Section: Discussionmentioning
confidence: 99%